2020
DOI: 10.1111/jcmm.15782
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone alleviates cisplatin nephrotoxicity by suppressing mitochondria‐mediated apoptosis via SIRT1/p53 signalling

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In this study, Rg1 pretreatment or pAD/Flag- AMPK α 1 stabilized MMP and reduced mPTP openness and mitochondrial Cyt C release to the cytosol (Figures 3 – 5 ). These results are consistent with previous reports [ 49 ]. More importantly, Rg1 pretreatment promoted mitochondrial respiratory chain complex NDUFB8 and UQCRC2 expression and ATP production.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, Rg1 pretreatment or pAD/Flag- AMPK α 1 stabilized MMP and reduced mPTP openness and mitochondrial Cyt C release to the cytosol (Figures 3 – 5 ). These results are consistent with previous reports [ 49 ]. More importantly, Rg1 pretreatment promoted mitochondrial respiratory chain complex NDUFB8 and UQCRC2 expression and ATP production.…”
Section: Discussionsupporting
confidence: 94%
“…SIRT1 is a nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylase that exerts anti-inflammatory and anti-oxidative effects on pathological process in several organs, including kidney 25 , 26 . In the present research, we found that TF inhibited CaOx-induced kidney oxidative stress injury and alleviated kidney crystal deposition by regulating miR-128/SIRT1 axis.…”
Section: Introductionmentioning
confidence: 99%
“…To further validate whether DBDCT induced apoptosis of HL7702 cells via the Gal-1-dependent pathway, the expressions of apoptosis-associated proteins in HL7702 cells were detected. e expressions of the antiapoptotic protein Bcl-2 and the proapoptotic protein Bax and p53 are crucial determinants of the apoptotic response mediated by many agents [38,39]. Accumulating evidence has shown that a decrease in the ratio of Bax/Bcl-2 inhibits Bax translocation to the mitochondria and then protects cells against apoptotic insults; however, a shift in the balance towards an excess of Bax evokes apoptosis [38,39].…”
Section: Discussionmentioning
confidence: 99%